(3GdGOGQI GdeGdjI GdOhdjI h GdJYGed HGdYedGJ GdGLfHjI (B/s - (3jhSa, Jhajb YHO GdQMje MSfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2010)
(3ejRGf GdeOahYGJ , GdfXGe GdfbOj , SYQ GdUQa GdGLfHj , JSejI CSYGQ GdYedGJ , CSYGQ GdYedGJ GdGLfHjI , GdeSJbHdjGJ , CSYGQ GdYedGJ GdCLfHjI , Mbhb GdNjGQ , YedjGJ GdJHOjd Ch GdebGjVI , GdGFJeGf , GdeDSSGJ GdeGdjI GdOhdjI , GdTQcGJ eJYOOI GdLfSjGJ (B.s
(3eQGLY U(B.253s
Keywords: (3GdGOGQI GdeGdjIs; (3GdGbJUGO GdeGdjs; (3GdYedGJ GdGLfHjIs; (3GdeGdjI GdOhdjIs